2004
DOI: 10.1021/ja048139n
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Dimerization Inhibitors of Wild-Type and Mutant HIV Protease:  A Focused Library Approach

Abstract: We demonstrate that a focused library based on truncated, cross-linked interfacial peptides of HIV-1 protease produces effective dimerization inhibitors of the enzyme. By combining individual changes of the library into a single compound, we obtained a significantly more potent agent and found that an additive increase in inhibitor efficacy was obtained. The good activity of library members against an active-site drug-resistant protease mutant bodes well for dimerization inhibition as a complementary method to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 14 publications
3
37
0
Order By: Relevance
“…A few groups have reported PR dimerization inhibitors targeting the terminal interface of PR (9)(10)(11)(12). However, none of such inhibitors have been of clinical utility, probably because PR dimers, once formed, are highly stable to "de-dimerize" with the potent dimerization forces in the termini interface (13).…”
Section: D25nmentioning
confidence: 99%
“…A few groups have reported PR dimerization inhibitors targeting the terminal interface of PR (9)(10)(11)(12). However, none of such inhibitors have been of clinical utility, probably because PR dimers, once formed, are highly stable to "de-dimerize" with the potent dimerization forces in the termini interface (13).…”
Section: D25nmentioning
confidence: 99%
“…Unlike all other crystal structures of the free protease, this 'monomeric' protease exhibits the closed flap conformation. Last but not least, there has been a continuing effort to design inhibitors of protease dimerization [54,55]. An interesting recent report [56] demonstrated that some of the inhibitors initially designed to prevent dimerization actually did not disrupt the dimer interface and yet showed substantial protease inhibition.…”
Section: Drug Design Targeting Protein Flexibility -New Allosteric Inmentioning
confidence: 99%
“…The most potent hit, PPBH3-1, bound Bcl-2 with a K d value of 52 ± 5 nM, corresponding to a 100-fold stronger binding affinity in comparison to Bak 72-87 [11]. The authors attributed this enhanced affinity to the rigid, pre-organization of the normally unstructured Bak [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87] binding epitope conferred by the -helix of aPP. Further studies probed the structural requirements for selective binding between the designed peptide motifs and two anti-apoptotic protein analogs, Bcl-2 and Bcl-x L [12].…”
Section: Miniature Protein Motifsmentioning
confidence: 99%
“…Focused libraries containing single and double mutations generated several potent small-molecule dimerization inhibitors of HIV-1 protease with the best inhibitor, 27, displaying a K i value of 29 nM (Fig. 13) [81][82][83].…”
Section: Crosslinked -Strand Mimetic Scaffoldsmentioning
confidence: 99%